Hubungan Regulasi Diri dengan Prokrastinasi Akademik - Sedyawati Sedyawati (Universitas Negeri Malang, 2021)
Abstract: Academic procrastination is a behavioral tendency to procrastinate tasks that occur in students. Factors that influence it include the lack of strategies in self-regulation or self-regulation (self-regulated learning). As one of the countries affected by the COVID-19 pandemic, Indonesia is implementing learning from home. In this condition, students are expected to have skills in managing themselves in learning during the learning process from home. This quantitative study examines the relationship between self-regulated learning and students' academic procrastination during the pandemic. The population of this research is the students of SMP Negeri 6 Malang, and the research sample uses random cluster sampling so that the number of students obtained is 168 consisting of class VII, class VIII, and class IX. The data collection uses a self-regulated learning scale and an academic procrastination scale on google forms distributed through online class Whatsapp groups. The data analysis technique used is a bivariate correlation to determine the relationship between the two variables. The data analysis results showed no significant relationship between self-regulated learning and students' academic procrastination. Abstrak: Prokrastinasi akademik merupakan kecenderungan perilaku menunda-nunda tugas yang terjadi pada siswa. Faktor yang mempengaruhi prokrastinasi akademik, antara lain kurangnya strategi pengaturan diri atau regulasi diri. Regulasi diri dibutuhkan siswa, terutama dalam kondisi kurang menguntungkan pada saat ini yaitu pandemi covid-19. Situasi saat ini menuntut siswa memiliki keterampilan mengatur diri yang baik agar terhindar dari kebiasaan menunda-nunda tugas. Tujuan penelitian ini untuk mengetahui hubungan antara regulasi diri dan prokrastinasi akademik selama pandemi covid-19. Populasi penelitian adalah siswa SMP Negeri 6 Malang, teknik pengambilan sampel menggunakan cluster random sampling dan diperoleh 167 siswa kelas VII, kelas VIII dan kelas IX. Pengumpulan data menggunakan skala regulasi diri dan skala prokrastinasi akademik. Teknik analisis data penelitian yaitu korelasi bivariat. Hasil analisis data menunjukkan bahwa tidak ada hubungan yang signifikan antara regulasi diri dengan prokrastinasi akademik siswa selama pandemi covid-19.